The Effect of Stem-Oriented Problem-Based Learning Model on Students' Critical Thinking Abilities on Rotation Dynamics Material - Abadi, Dendy Surya; Fatmawati, Sri; Azizah, Nadia (Universitas Tidar, 2025)
In the era of modern learning that increasingly emphasizes high-level thinking competencies, various innovative learning methods continue to be developed to improve the quality of education. One important aspect of the learning process is critical thinking skills that need to be developed early on in students, especially in subjects that require in-depth analysis such as physics. This study examines the impact of the STEM-integrated Problem-Based Learning (PBL) approach on students' critical thinking skills, especially in the context of rotational dynamics content. The PBL model is integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach, where STEM elements are applied consistently throughout the learning process. The experiment is a type of research. This study used a quasi-experimental method with a posttest-only non-equivalent control group design. The study sample consists of a control and an experimental group. The essay assessment used for examination was validated through hypothesis testing using SPSS 27 software. The data collection technique used a posttest given to the control and experimental classes after treatment. Posttest results indicated improvement in both the experimental and control groups. Based on independent test results, the two-tailed significance level, 0,006 < 0,05, and the t-value of 2,79 > 1,663 (t table) show that the experimental and control groups differ significantly. A considerable difference exists in the performance offered at the student critical thinking level when the t count value is bigger than the t table. It can be inferred from applying the Problem-Based Learning paradigm in education that there are serious drawbacks.